Rainouts over the Arabian Sea and Western Ghats during moisture advection and recycling explain the isotopic composition of Bangalore summer rains. Issue 11 (2nd June 2016) - Rahul, P.; Ghosh, Prosenjit; Bhattacharya, S. K.
Abstract: Variations in the isotope ratios ( 18 O/ 16 O and D/H) of meteoric water at continental stations serve as valuable tracers for the hydrological cycle. In the present study, we investigated the role of sea surface temperature, wind speed, relative humidity, and rainout processes on the stable isotopic composition of the 2010 monsoon rainwater of Bangalore. The wind over the ocean influences the sea surface temperature and humidity which in turn influence the vapor isotopic composition. The rainout over the Arabian Sea and the land mass (Western Ghats) during advection of the air parcel to Bangalore and its recycling further modify the vapor composition. The isotopic ratios ( δ 18 O, δ D, and d ‐excess) of the precipitation at Bangalore was estimated following a Rayleigh fractionation model involving rainout and recycling processes yield values consistent with our observation. In some samples, however, the observed isotopic ratios are higher (by 2 to 5‰), and a few of them are associated with high d ‐excess values. These discrepancies could be due to limitation of the model assumptions. Key Points: First detailed comparison of isotope with source conditions Intraseasonal stable isotope variability of Indian summer monsoon Model explanation of observed data